Acidified milk for feeding dairy calves in tropical raising systems - Coelho, M. G. (2020)
The objective of this study was to evaluate the effect of milk acidification in tropical climate conditions on dairy calves’ growth, health and selected blood metabolites. Thirty-two Holstein calves were blocked according to sex, birth date and weight, and distributed to the following treatments: 1. refrigerated milk kept at 5 °C (RM) or 2. acidified milk (with added lactic acid to a pH of 4.2) kept at ambient temperature (ACM). After birth, calves were fed colostrum and from the second day received 6 l/day of RM or ACM heated to 38 °C until weaning at day 56. Calves were individually housed with free access to water and starter diet. Feed intake and health problems were monitored daily; calves were weighed and measured weekly. Blood samples were collected weekly to evaluate the levels of metabolites. Feed intake, body weight and daily gain did not differ between treatments, but heart girth and wither height was higher for animals fed RM. The faecal score was lower for RM group, however in calves fed ACM it also did not suggest a diarrheal process (1.98). In addition, the first case of diarrhoea in calves fed ACM was later than in calves fed RM (15.4 vs 8.6 days, respectively; P < 0.01). So, the acidification of milk is an adequate method of preserving milk in tropical ambient temperatures. It resulted in health benefits to calves, delaying the first case of diarrhoea.